2017
DOI: 10.1002/jcla.22306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prenatal diagnosis of alpha and beta thalassemia in pregnant Hakka women in southern China

Abstract: Our findings provide key information for clinical genetic counseling of prenatal diagnosis for major thalassemia in pregnant Hakka women in southern China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The results in the present study are similar to those of other studies. 37 , 38 , 39 Some genes in chromosome 16 have been associated with diseases such as thalassemia, 40 prenatal growth retardation, 41 abnormal fetal head circumference 42 and autism. 43 One study found that CNVs on chromosome 16 play an important role in the determination of developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…The results in the present study are similar to those of other studies. 37 , 38 , 39 Some genes in chromosome 16 have been associated with diseases such as thalassemia, 40 prenatal growth retardation, 41 abnormal fetal head circumference 42 and autism. 43 One study found that CNVs on chromosome 16 play an important role in the determination of developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, the higher thalassemia prevalence in Hakka population that shown in our research may be related to the selection of the subjects. [ 10 12 , 21 ] Most of our subjects are hospitalized patients, not random large crowd, which is also a limitation of this study. If we can effectively control of the birth of severe thalassemia in this region, it will produce huge social and economic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, population in different regions has their own spectrums of thalassemia (7). At present, it is reported thalassemia is widely distributed on the southern China, particularly in the provinces of Guangdong (8), Guangxi (9), and Hainan (10). Yunnan which have a high frequency of thalassemia is located in the southwestern of China at the junction of Guangxi, Guizhou, and Sichuan provinces (11).…”
Section: Introductionmentioning
confidence: 99%